2019
DOI: 10.1177/0308022619876558
|View full text |Cite
|
Sign up to set email alerts
|

Boredom in inpatient mental healthcare settings: a scoping review

Abstract: Introduction To identify the scope of existing literature exploring boredom experienced by those using inpatient mental health services, we conducted a scoping review. Method We performed a comprehensive literature search of four databases: Medline, EMBASE, CINAHL and PsycINFO. This search resulted in 978 titles and abstracts, which were reviewed by two independent raters. Results A total of 19 studies met the criteria for inclusion. Inter-rater reliability was assessed (k = 0.719 (95% confidence interval … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 41 publications
(109 reference statements)
3
23
0
Order By: Relevance
“…Boredom is a common experience for consumers in acute units (Marshall et al., 2019). Participants in this study highlighted the negative impact of a lack of meaningful activities on their feelings of safety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boredom is a common experience for consumers in acute units (Marshall et al., 2019). Participants in this study highlighted the negative impact of a lack of meaningful activities on their feelings of safety.…”
Section: Discussionmentioning
confidence: 99%
“…Having meaningful activities supports safety by promoting choice, autonomy and connection to self and others (Fletcher, Hamilton, Kinner, Sutherland, et al, 2019). In contrast, lack of meaningful activities can mean that consumers become bored (Muir‐Cochrane et al., 2013), and negative thoughts can flourish (Molin et al., 2016), thus increasing the potential for aggression (Marshall et al., 2019) and risk of absconding (Muir‐Cochrane et al., 2013). The availability of meaningful activities is supportive of consumers' safety while also facilitating recovery by promoting choice, autonomy and connection to self and others (Fletcher, Hamilton, Kinner, Sutherland, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence for initiatives which have tried to improve the therapeutic qual ity of wards, such as scheduling protected time for ward staff to engage with patients, has tended to be inconclusive. Boredom is identified as a common problem for patients on inpatient wards, but further empirical evidence is needed about its im pacts and the best ways to address it 88 .…”
Section: Management Of Crises In Hospitalmentioning
confidence: 99%
“…In the literature review 'Impact of boredom on mental health', Marshall et al (2019) concluded that 'occupational therapists play an important role in addressing the boredom experienced by those receiving treatment for mental illness in hospital settings'.…”
Section: Kirby M Occupational Therapistmentioning
confidence: 99%